2015
DOI: 10.1146/annurev-phyto-080614-120207
|View full text |Cite
|
Sign up to set email alerts
|

Range-Expanding Pests and Pathogens in a Warming World

Abstract: Crop pests and pathogens (CPPs) present a growing threat to food security and ecosystem management. The interactions between plants and their natural enemies are influenced by environmental conditions and thus global warming and climate change could affect CPP ranges and impact. Observations of changing CPP distributions over the twentieth century suggest that growing agricultural production and trade have been most important in disseminating CPPs, but there is some evidence for a latitudinal bias in range shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
189
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(194 citation statements)
references
References 149 publications
(181 reference statements)
3
189
1
1
Order By: Relevance
“…Among 612 species of pests and pathogens, investigators observed an average poleward shift of 2.7 km per year since 1960 (13). Crops often lack defenses against nonnative pests and pathogens (12), requiring ongoing breeding and management efforts to face new threats. Spatial mismatches between pests and natural predators can also undermine biological control systems (134).…”
Section: Pestsmentioning
confidence: 99%
“…Among 612 species of pests and pathogens, investigators observed an average poleward shift of 2.7 km per year since 1960 (13). Crops often lack defenses against nonnative pests and pathogens (12), requiring ongoing breeding and management efforts to face new threats. Spatial mismatches between pests and natural predators can also undermine biological control systems (134).…”
Section: Pestsmentioning
confidence: 99%
“…However, predictions on future outbreak dynamics of defoliators remain uncertain as there is conflicting evidence on outbreak severity [20]. In general, poleward and upward shifts of pests and pathogens have been documented, but predictions are complicated due to interactions and uncertainties associated with changing weather patterns, extreme climate events, and differing responses of plants and insects to these events [21]. The consequences of higher frequency of extreme events are still poorly documented.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in phenology and phenological mismatches with host trees and/or natural enemies can alter trophic relationships and either favor or be detrimental to forest insect populations [34,35]. Physiological changes in insects in response to temperature can facilitate changes in their distribution patterns [21]. Field-based experimental manipulations of host plants [36] and insects to determine their relative responses to changes in temperature [37][38][39] can help predict the nature and extent of range shifts and to better understand how forest ecosystems will respond to climate change [40].…”
Section: Introductionmentioning
confidence: 99%
“…The intimate relationship between plants and herbivores, which in some cases results in devastating crop losses, will be altered by global climate change. In the case of arthropods, the increase in temperature will shorten their life cycle, having as consequences more generations per year and an earlier appearance of the pest (Luedeling et al, 2011;Delucia et al, 2012;Bebber, 2015). In addition, phytophagous pests will expand their distribution area as a consequence of increases in northern temperatures, a process that will be helped by trade, a factor responsible for introduction of invasive species (Parmesan, 2006;Meynard et al, 2013;Bebber, 2015).…”
mentioning
confidence: 99%
“…In the case of arthropods, the increase in temperature will shorten their life cycle, having as consequences more generations per year and an earlier appearance of the pest (Luedeling et al, 2011;Delucia et al, 2012;Bebber, 2015). In addition, phytophagous pests will expand their distribution area as a consequence of increases in northern temperatures, a process that will be helped by trade, a factor responsible for introduction of invasive species (Parmesan, 2006;Meynard et al, 2013;Bebber, 2015).To increase food security it is crucial to reduce crop losses due to biotic and abiotic stresses. Among the different abiotic stresses, water shortage is considered to be the most damaging to crop productivity and it is expected to cause global grain yield losses of up to 30% an estimated 14% crop loss, plant pathogens about 13%, and weeds a 13% loss worldwide.…”
mentioning
confidence: 99%